Dinamika Post-Traumatic Growth Pada Ibu Pendiri Rumah Qu’ran Pasca Kematian Anak Usia Dewasa Awal - Adzra Ayu Haafidah; Retno Pangestuti (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2026)
Background: The death of a child in early adulthood is a traumatic experience that has a profound impact on parents, especially psychologically, emotionally, socially, and spiritually. Because early adulthood is a crucial age, having a closer emotional attachment Objective: This study aims to explore the dynamics of Post-Traumatic Growth (PTG) experienced by a Muslim mother after the loss of her early adult child Method: The research method used is a qualitative case study with data collection through in-depth interviews, observation and documentation. Results: The results of the study show that after experiencing an initial setback, the informant experienced positive growth in five aspects of PTG, namely appreciation of life, relationships with others, personal strength, new possibilities in life, and changes in spirituality. The establishment of a Qur'an House in the name of the deceased child, distribution of mushafs, spiritual transformation especially through understanding the interpretation of Surah Al-Baqarah verse 216 and increased solemnity in prayer and consistency of tahajud, play a key role in the recovery process. Conclusion: This study confirms that social support, spiritual integration, and new meanings of the grief experience are important factors in facilitating post-traumatic growth in Muslim mothers who have lost a child. Keywords: Post-Traumatic Growth, Deceased Child, Mother